Feminisms at Work: The (Re)Production of Gender and Culture in Contemporary Galicia - Barbour, Catherine (My University, 2022)
Dynamic, multifaceted and multimodal feminist and woman-led artistic production has made its mark in the Galician cultural sphere in recent years. Non-canonical artistic formulations located on the fringes of, and often serving as a challenge to, mainstream Galician culture reveal new ways of thinking about gender from peripheral, non-hegemonic and decolonial positions. Galician women are engaging in creative and experimental forms of self-expression, self-production and consumption of culture by reconfiguring and ‘refashioning’ Galician feminisms and femininities within a global framework. Particularly timely in the wake of the #MeToo movement, 8M women’s strikes and the impact of the COVID-19 pandemic on gender equality, and with social media playing an ever more prominent role in the diffusion of grassroots feminist activism, contemporary Galician creative practice by, for and about women has much to teach us in how it challenges heteropatriarchal binaries and stereotypes.
PUBLISHED
Special Issue: (Re)Producing Galician Femininities ed. by Catherine Barbour and Danny Barreto
Keywords: Identities in Transformation; Inclusive Society; Galician Studies; Gender; Literature